The paradoxical impacts of anti-cigarette campaigns in Indonesia: Between production increase and the faith of small-scale tobacco farmers - Bagong Suyanto (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This article explains the extent to which the anti-tobacco campaigns have brought about a paradoxical impact on Indonesian small-scale tobacco farmers. It draws on empirical studies undertaken in four areas of the Eastern Java Province, and involves 300 respondents. The findings of the survey indicate that while anticigarette campaigns have affected and restricted tobacco production, big distributors and multinational tobacco companies are enjoying more profits. In contrast, small-scale farmers are suffering from more losses caused by mainly three interrelated factors; the narrowing margin of profit, increasingly difficult access to sell tobacco products, and weak bargaining position in the face of the tobacco market.